ANALISIS NILAI TAMBAH USAHA PENGOLAHAN GULA AREN DI DESA KANDANGAN LAMA KECAMATAN PANYIPATAN KABUPATEN TANAH LAUT - Tutus Septiawan; Magdalena Yoesran (Jurnal Sylva Scienteae, 2020)
This study aims to calculate the added value obtained from processing palm sugar in the Kandangan Lama village, Panyipatan district, Tanah Laut Regency. Determination of the study area was done purposively. The sampling method is using the purposivedsampling method. The data was collected consists of primaryaandasecondary data. The data analysis was using the Hayami Method. Based on the results of the study showed that the added value obtained from processing palm sugar ranged from Rp 4,042.7, - with a valueeaddedaratio of 29.3%.Keywords: palm sugar; add value and income